Integrity shots; contemporary indigenous research to reconcile with standards (part 2) - Haider, Nighat; Dogar, Imtiaz Ahmad (Journal of Pakistan Psychiatric Society, 2021)
In the first part of the script, we explored the need for researching integrity in research and mapped out what psychiatric community can do to implement the scientific integrity in research. In continuation to the previous, this part focuses upon identifying the loop holes in integrity of research that we had been receiving in past seven years as editors. Integrity in research implies that planning, implementation and analysis of the research projects be honest and replicable1. We see many shared values2 of scientific research being ignored not at these three steps but also while reporting and publishing as well.